Assessment of different feedstocks in South Tyrol (Northern Italy): Energy potential and suitability for domestic pellet boilers. (July 2016) - Prando, Dario; Boschiero, Martina; Campana, Daniela; Gallo, Raimondo; Vakalis, Stergios; Baratieri, Marco; Comiti, Francesco; Mazzetto, Fabrizio; Zerbe, Stefan
Abstract: The present study aims to quantify the main biomass resources in South Tyrol (Northern Italy) and estimate the potential contribution for the energy sector. Moreover, four representative feedstocks have been tested in a domestic pellet boiler under standard conditions in order to assess its performance and pollutant emissions. The unexploited biomass potential for energy conversion applications, expressed as dry weight, has been estimated to be 135 000 t y −1 from forest, 14 950 t y −1 for apple pruning residues and 12 000 t y −1 from the industrial sector. The scenario of utilizing the unexploited local biomass resources – in energy systems such as the ones deployed in South Tyrol – would contribute with an annual bioenergy production contribution of 130–270 TJ of electricity and 1700–2100 TJ of heat. Finally, the tested feedstocks can be used in domestic boilers, however, some modifications are required when using agricultural residues. Highlights: A considerable unexploited biomass share could be used in the energy sector. In South Tyrol the energy from biomass could be sustainably increased by 20%. Similar efficiencies (≈86%) for the boiler operated with the analysed feedstocks. Emissions within the European limits except for dust emissions of agro-residues.